Creation of microenterprises and sociocultural factors (2022)
Analyzing and identifying the most predominant processes that have been considered by the microentrepreneurs at the time of making the decision to create their business is fundamental, delving into the sociocultural factors that affect the behavior of people. The methodology applied is framed within the empirical-inductive epistemological approach, with a non-experimental field research design. The data analysis was carried out using a regression model with an adjusted R-squared of 0.772. The creation of microenterprises, to a lesser extent, is the product of the consolidation of a family business, the lack of employment or a dismissal; on the opposite, greater significance is identified when relating previous experience with the development of a business opportunity.